2008
DOI: 10.5433/1679-0359.2008v29n3p693
|View full text |Cite
|
Sign up to set email alerts
|

A importância dos animais de produção na infecção por Toxoplasma gondii no Brasil

Abstract: A importância dos animais de produção na infecção porToxoplasma gondii no BrasilThe importance of food animals in the infection for Toxoplasma gondii in Brazil patricia Riddell Millar * ; Leila Gatti Sobreiro ; Isabel Cristina Fábregas Bonna ; Maria Regina Reis Amendoeira ResumoA toxoplasmose é uma das infecções parasitárias mais prevalentes no homem e nos animais, e a sua transmissão tem sido usualmente atribuída à ingestão de carnes cruas ou mal cozidas, de animais de produção infectados, sendo a taxa de inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 0 publications
0
20
1
9
Order By: Relevance
“…Analysis of the municipality distribution showed an infection rate of 71.43% in the city of Pedra (15/21). Although production animals like sheep were found to be more susceptible to infection than other species (MILLAR et al, 2008), serological studies have confirmed the distribution of T. gondii infection in sheep with variable percentages (TENTER et al, 2000). The prevalence of seropositive animals found in this study (13.60%) was lower than the results found in other Brazilian states (LANGONI et al, 1999;PINHEIRO JÚNIOR et al, 2009).…”
Section: Resultscontrasting
confidence: 56%
“…Analysis of the municipality distribution showed an infection rate of 71.43% in the city of Pedra (15/21). Although production animals like sheep were found to be more susceptible to infection than other species (MILLAR et al, 2008), serological studies have confirmed the distribution of T. gondii infection in sheep with variable percentages (TENTER et al, 2000). The prevalence of seropositive animals found in this study (13.60%) was lower than the results found in other Brazilian states (LANGONI et al, 1999;PINHEIRO JÚNIOR et al, 2009).…”
Section: Resultscontrasting
confidence: 56%
“…In a study on the importance of farm animals for T. gondii infection in Brazil, it was concluded that cats were the key to controlling toxoplamosis 39 . In the present study, a statistically significant association was found between seropositivity for toxoplasmosis and contact with cats (p=0.039).…”
Section: Resultsmentioning
confidence: 99%
“…Caprinos e ovinos infectados por T. gondii representam uma fonte de infecção importante para os seres humanos, devido à ingestão de leite in natura e carne crua ou mal cozida contaminados destes animais (Millar et al 2008).…”
Section: Introductionunclassified